U.S. Foreign Policy Towards Unesco After Acceptance Of Palestinian Membership For The Period 2012-2017 - Machmudi, Yon; Qudsi Ardifansyia, Qothrunnada Quraissyn (Journal of Strategic and Global Studies, 2022)
The United States is one of the countries that established Palestine as a state. The struggle for Palestine to get full membership status in the United Nations (UN) also often gets a veto from the United States. The United States rejects Palestine at UNESCO because according to America, membership status as a country cannot determine the decision of the UN Security Council first. The research method used in this research is descriptive research method, and the writer will use secondary data. This paper examines the United States' policy towards UNESCO after the membership of Palestine for the 2012-2017 period. The conclusion of this research is that the United States officially left UNESCO after Palestine joined the organization.